2006
DOI: 10.1086/501356
|View full text |Cite
|
Sign up to set email alerts
|

Linezolid-Induced Inhibition of Mitochondrial Protein Synthesis

Abstract: These results provide direct evidence that linezolid inhibits mitochondrial protein synthesis with potentially severe clinical consequences. Prolonged courses of linezolid should be avoided if alternative treatment options are available.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
179
1
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 275 publications
(187 citation statements)
references
References 23 publications
6
179
1
1
Order By: Relevance
“…The risk for linezolidinduced lactic acidosis is associated with duration of therapy [28], but early linezolid-induced lactic acidosis has also been reported [29]. Some studies using cell-culture experiments have suggested that linezolid toxicity is caused by inhibition of mitochondrial protein synthesis [30][31][32]. There is some evidence that polymorphisms in the mitochondrial 16S ribosomal RNA (rRNA) (e.g., A1036G) may contribute to severe linezolid-associated lactic acidosis in adults [33,34].…”
Section: Pathophysiologymentioning
confidence: 99%
“…The risk for linezolidinduced lactic acidosis is associated with duration of therapy [28], but early linezolid-induced lactic acidosis has also been reported [29]. Some studies using cell-culture experiments have suggested that linezolid toxicity is caused by inhibition of mitochondrial protein synthesis [30][31][32]. There is some evidence that polymorphisms in the mitochondrial 16S ribosomal RNA (rRNA) (e.g., A1036G) may contribute to severe linezolid-associated lactic acidosis in adults [33,34].…”
Section: Pathophysiologymentioning
confidence: 99%
“…In this way, the protein subunits within each OXPHOS complex were separated (Devreese et al 2002). The twodimensional (2D) gels were electro-blotted onto a nitrocellulose membrane using a tank blotting apparatus from Bio-Rad, as has been described previously (De Vriese et al 2006). The relative levels of the five OXPHOS complexes were evaluated by immunodetection, using the MS601 MitoProfile® human total OXPHOS complexes detection kit from MitoSciences in a 1/1000 dilution.…”
Section: Enzyme Assaysmentioning
confidence: 99%
“…Prolonged courses of linezolid have been associated with lactic acidosis and optic or peripheral neuropathy and appear to inhibit mitochondrial protein synthesis. 28,29,30 It would therefore be advisable not to co-administer other drugs, which suppress mitochondrial activity such as didanosine, stavudine, and to a lesser extent zidovudine. Clofazimine: Clofazimine is a substituted iminophenazine bright-red dye that inhibits mycobacterial growth and binds preferentially to mycobacterial DNA causing inhibition of transcription.…”
mentioning
confidence: 99%